The development of the grammatical competence through direct corrective feedback among ninth-year a students at La Dolorosa high school of the city of Loja during the 2016-2017 school year - Montaño Ordóñez, Deice Natali (2018)
This research was focused on the development of the grammatical competence through the direct corrective feedback at La Dolorosa high school amongst 37 students for 8 weeks. The following methods were used to carry out this investigation: the analytic/synthetic method; the statistic method; the scientific method and the descriptive method. The instruments used were a pre-and post- test and a pre-and post-questionnaire. The results indicated that direct corrective feedback provided a positive support on the improvement of the students’ grammatical skills. The study concluded that, using direct corrective feedback is an effective strategy for students to recognize and reduce their grammatical errors, achieving a satisfactory improvement in their grammatical competence.